Changes in Burnout Among Oncology Physician Assistants Between 2015 and 2019. Issue 1 (January 2022) - Tetzlaff, Eric D.; Hylton, Heather M.; Ruth, Karen J.; Hasse, Zachary; Hall, Michael J.
Abstract : PURPOSE: Burnout has significant implications for the individual provider, the oncology workforce, and the quality of care for patients with cancer. The primary aim of this study was to explore temporal changes in burnout among physician assistants (PAs) in oncology in 2019 compared with 2015. METHODS: Oncology PAs were surveyed to assess for burnout using the Maslach Burnout Inventory according to the same cross-sectional design of the study performed in 2015. Comparison between oncology PAs in 2015 and 2019 in the prevalence of burnout and personal and professional characteristics was performed. RESULTS: Two hundred thirty-four participants completed the full-length survey. The participants in 2015 and 2019 were similar in age (41.8 v 40.3 years), sex (88.8% v 86.3% female), number of years as a PA in oncology (9.6 v 10), and percentage involved in academic practice (55.2% v 59.2%). There was a significant increase in burnout in 2019 compared with 2015 with 48.7% of PAs reporting at least one symptom of burnout compared with 34.8% (odds ratio for burnout, 2019 v 2015 = 1.92 [95% CI, 1.40 to 2.65], P < 0.001). The odds of burnout remained higher in 2019 compared with 2015 when adjusted for age, sex, relationship status, practice setting, subspecialty, practice type, and hours worked. Factors associated with burnout in both 2015 and 2019 include the percentage of time spent on patient care, collaborative physician relationship, number of hours worked, and satisfaction with compensation. No new factors associated with burnout emerged in 2019 that were not identified in 2015. CONCLUSION: The rate of burnout of oncology PAs has significantly increased. Burnout in oncology PAs is multifactorial, and the increase cannot be easily explained. Additional research is needed to better define the drivers of PA burnout.